Scalability of MIMO Antennas: Assessing Gain and HPBW for Different Antenna Element Configurations - Salsabila, Salwa; Ryanu, Harfan Hian; Nur, Levy Olivia; Nugroho, Bambang Setia (Jurnal Rekayasa Elektrika, 2024)
The design of Massive MIMO Antennas presents challenges due to their large size, which can impede the design process. Additionally, the arrangement of multiple antenna elements in Massive MIMO Antennas poses a challenge, as it surpasses the capabilities of simulation software and involves complex procedures. Therefore, to address these issues, a scalability technique utilizing array factor theory is employed to determine the relationship between the configuration of MIMO antennas and the corresponding values of gain and half-power beamwidth (HPBW). By utilizing a simpler MIMO Antenna array with incremental configurations, such as 2x2, 4x4, 8x8, and 16x16 MIMO element schemes, the array factor theory allows for the prediction of the gain and HPBW values for a Massive MIMO Antenna array with a specific configuration. This research aims to explore the scalability process and derive equations that relate the gain and HPBW values to the different MIMO configurations. The designed MIMO antenna arrangement is based on rectangular antennas with truncated corners and circular antennas with X slots, allowing for the investigation of various configurations operating at a frequency of 3.5 GHz.